The blue-green path to urban flood resilience. Issue 1 (2nd December 2019) - O'Donnell, Emily; Thorne, Colin; Ahilan, Sangaralingam; Arthur, Scott; Birkinshaw, Stephen; Butler, David; Dawson, David; Everett, Glyn; Fenner, Richard; Glenis, Vassilis; Kapetas, Leon; Kilsby, Chris; et al.
Abstract: Achieving urban flood resilience at local, regional and national levels requires a transformative change in planning, design and implementation of urban water systems. Flood risk, wastewater and stormwater management should be re-envisaged and transformed to: ensure satisfactory service delivery under flood, normal and drought conditions, and enhance and extend the useful lives of ageing grey assets by supplementing them with multi-functional Blue-Green infrastructure. The aim of the multidisciplinary Urban Flood Resilience (UFR) research project, which launched in 2016 and comprises academics from nine UK institutions, is to investigate how transformative change may be possible through a whole systems approach. UFR research outputs to date are summarised under three themes. Theme 1 investigates how Blue-Green and Grey (BG + G) systems can be co-optimised to offer maximum flood risk reduction, continuous service delivery and multiple co-benefits. Theme 2 investigates the resource capacity of urban stormwater and evaluates the potential for interoperability. Theme 3 focuses on the interfaces between planners, developers, engineers and beneficiary communities and investigates citizens' interactions with BG + G infrastructure. Focussing on retrofit and new build case studies, UFR research demonstrates how urban flood resilience may be achieved through changes in planning practice and policy to enable widespread uptake of BG + G infrastructure.